Benzyl and fluorinated benzyl side chains for perylene diimide non-fullerene acceptors12. (17th October 2018) - Nazari, Maryam; Martell, Mark; Welsh, Thomas A.; Melville, Owen; Li, Zhe; Cann, Jonathan; Cieplechowicz, Edward; Zou, Yingping; Lessard, Benoit H.; Welch, Gregory C.
Abstract : The synthesis, characterization, and photovoltaic performance of three N -annulated perylene diimide dimers with benzyl based side-chains is reported. Abstract : The synthesis and characterization of three N -annulated perylene diimide dimers with benzyl based side-chains is reported. Benzyl, 4-fluorobenzyl, and pentafluorobenzyl groups are used as side chains at the pyrrolic N-atom position of the N -annulated perylene diimide chromophore. All three compounds were used as non-fullerene acceptors in polymer based organic solar cells. Power conversion efficiencies upwards of 5.8% were achieved for both benzyl and 4-fluorobenzyl substituted acceptors, with different donor polymers.